Thymosin alpha 1 alleviates inflammation and prevents infection in patients with severe acute pancreatitis through immune regulation: a systematic review and meta-analysis - Tian, Yong; Yao, Jiaqi; Ma, Yihan; Zhang, Pengcheng; Zhou, Xiaofang; Xie, Wenjie; Tang, Wenfu (Frontiers in Immunology, 2025)
BackgroundImmune and inflammatory disorders are part of the complex pathophysiological processes that exacerbate severe acute pancreatitis (SAP) and subsequent infection. Thymosin alpha 1 (Tα1) is an important immunomodulatory agent in clinical practice, but there is a lack evidence to prove its effectiveness in improving the condition of SAP patients. In this study, we aimed to evaluate the efficacy in meta-analysis.MethodsWe systematically searched PubMed, Embase, Web of Science, Cochrane Library and China National Knowledge Infrastructure (CNKI) up to February 1, 2025. Randomized controlled studies comparing the efficacy of Tα1 as intervention measure with non-Tα1 in improving immune regulation for patients with SAP were included. Review Manager 5.3 was used to assess endpoints in the meta-analysis.ResultsFive randomized controlled trials comprising 706 patients with SAP were included. The results indicated that Tα1 could increase the percentages of CD4+ cells (MD=4.53, 95%CI [3.02, 6.04], P<0.00001) and improve the CD4+/CD8+ ratio (MD=0.42, 95%CI [0.26, 0.58], P<0.00001) in SAP patients. There was no statistically significant decrease in CD8+ cells. For inflammation, lower-dose Tα1 could significantly reduce C-reactive protein (CRP) levels (mg/L) (MD=-30.12, 95%CI [-35.75, -24.49], P<0.00001), while higher-dose Tα1 showed no statistically significant difference (MD=-3.83, 95%CI [-12.14, 4.49], P=0.37). In terms of infection, the immunomodulatory therapy of Tα1 obviously reduced the overall incidence of extrapancreatic infections in SAP patients (RR=0.56, 95%CI [0.40, 0.78], P=0.0005), especially for blood (RR=0.60, 95%CI [0.38, 0.94], P=0.03) and abdominal (RR=0.38, 95%CI [0.19, 0.78], P<0.0001), while the reduction in lung infections was not statistically significant. Regarding hospital stay (days), Tα1 did not significantly reduce the time spent (MD=-4.22, 95%CI [-11.53, 3.10], P=0.26). However, Tα1 reduced the APACHE II score (MD=-1.52, 95%CI [-2.22, -0.83], P<0.0001).ConclusionTα1 can regulate the balance of immune cells and alleviate immune suppression in SAP patients, including increasing CD4+ T cells and CD4+/CD8+ ratios. Tα1 may exert anti-inflammatory and extrapancreatic infection-preventive effects on SAP patients and improve their condition or prognosis. More researches are needed to validate the results.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024570517.